Cryopreservation of Pelargonium species by dropletvitrification - Gallard, A; Préveaux, Anne; Audin, N; Dorion, N; Grapin, Agnes (MTT, 2008)
In order to guarantee safe, long-term conservation of the National Institute of Horticulture (I.N.H.) Pelargonium collection, meristem cryopreservation studies have been undertaken since 1999. An encapsulation-dehydration process has been first developed. More recently, studies were undertaken in order to adapt the droplet-vitrification procedure (1) to this genus. In order to optimize the process, its main steps were studied choosing P. x peltatum 'Balcon Lilas' as a model, using plants grown in a greenhouse. The best results were obtained dehydrating apices in two steps, 20 min in LS and 15 min in PVS2 and then immersing them directly in Liquid Nitrogen (LN). After thawing and unloading in the recovery solution at room temperature during 15 min, apices were regenerated onto a semi-solid medium (2). This simple protocol without any pretreatment, was tested on 28 different Pelargonium accessions representative of the diversity of our collection. For each accession, at least 3 repetitions were performed on different days, reaching a minimum of 24 cryopreserved apices per genotype. An average of 65% survival rate was obtained ranging from 14.8% for P. fragans to 90% for P. capitatum and P. x hortorum Neurot. Plants were regenerated for each genotype, except P. x peltatum Papa Crousse. The genotype dependent tolerance at each step of the process is discussed.
Keywords: Ka; Pelargonium x peltatum; dehydrating; Pelargonium fragans; Pelargonium capitatum; Pelargonium x hortorum